THE ROLE OF INFORMATION TECHNOLOGY IN BUSINESS GROWTH PERFORMANCE IN KOSOVA - AFERDITA BERISHA-SHAQIRI (Challenges of the Knowledge Society)
As a result of rapid development of information technology and its fast application in the economy and business processes, it has come to the transformation of industrial society to information society while the information society is the new feature of human civilization, where services have become universal and increased the role and importance of information and knowledge.Today the economy is transformed from the classical model in a new model known as the "knowledge economy" or "global economy". In terms of the knowledge economy in order to create competitive advantage, businesses must be innovative in information technology since information technology has become an integral part of organizational strategy and planning processes and the way to create and enhance competitiveness. Given current trends in the computerization of enterprises worldwide scale is imperative that Kosovo enterprises to transform into computerized enterprise.